1996
DOI: 10.1080/01904169609365212
|View full text |Cite
|
Sign up to set email alerts
|

Mineral nutrient transport by sunflower seedlings grown under saline conditions (NaCl)

Abstract: Sunflower seeds (Helianthus annuus L., cv. Dwarf) were grown with distilled water only or increasingly saline solutions (NaCl) to determine the influence of salinity on seedling growth and on the distribution of mineral nutrients obtained exclusively from cotyledons. Seedling growth was decreased by moderate (50mM) and high (l00mM) concentrations of NaCl in the growth solution. Salinity generally decreased mineral transport (especially Fe, Mn, Mg, and Ca) from seed to seedling, except for K. Transport of Fe, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…2000). In addition to this, Sanchez‐Raya and Delgado (1996) reported that salinity reduced the Fe 3+ and Mn 2+ contents in sunflower seedlings.…”
Section: Introductionmentioning
confidence: 67%
“…2000). In addition to this, Sanchez‐Raya and Delgado (1996) reported that salinity reduced the Fe 3+ and Mn 2+ contents in sunflower seedlings.…”
Section: Introductionmentioning
confidence: 67%
“…In our experiments, the saline stress reduced the Ca 2+ and Mg 2+ concentrations only in the shoots, while in the roots they remained constant. This effect has been reported in other species such as Helianthus annuus [28] or Solanum melongena [29]. Lynch and Läuchli [16] proposed that the decrease in the concentration of these cations in the shoots may be related to the reduced Ca 2+ release into the root xylem, possibly by affecting the cation active loading in the xylem vessels.…”
Section: Discussionmentioning
confidence: 95%
“…In the same way, concentrations of Fe, Mn and Zn in leaves of zucchini were increased by intensifying the salt stress; however, the concentration of Cu was reduced [10]. Moreover, Sanchez-Raya and Delgado suggested that salinity generally decreased Fe and Mn transportation from seed to seedling in the growth period in sunflower plants [11]. They also reported that transportation of Fe to aerial parts was distinctly reduced.…”
Section: Introductionmentioning
confidence: 90%